Using Basic on the IBM personal computer - Sondak, Norman E. (SRA, 1985)
What is Structured Methodology and Why is it Important ?, Getting Started on the computer, The Basics of BASIC, The Program Development Process, Common Devices Used in Data Processing Programs, Producing Business Reports, more about looping...